2010
DOI: 10.3390/md8112781
|View full text |Cite
|
Sign up to set email alerts
|

Marine Bacterial Sialyltransferases

Abstract: Sialyltransferases transfer N-acetylneuraminic acid (Neu5Ac) from the common donor substrate of these enzymes, cytidine 5′-monophospho-N-acetylneuraminic acid (CMP-Neu5Ac), to acceptor substrates. The enzymatic reaction products including sialyl-glycoproteins, sialyl-glycolipids and sialyl-oligosaccharides are important molecules in various biological and physiological processes, such as cell-cell recognition, cancer metastasis, and virus infection. Thus, sialyltransferases are thought to be important enzymes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 71 publications
1
16
0
Order By: Relevance
“…These enzymes catalyse the transfer of Sia (Neu5Ac or another derivative of sialic acid) from its activated sugar nucleotide donor, CMP-sialic acid, to an acceptor [90]. They govern addition of Sia with α-2,3-or α-2,6-linkage to the terminal galactose, with α-2,6-linkage to the terminal GalNAc or with α-2,8-linkage to the terminal Sias [99].…”
Section: Sialyltransferasesmentioning
confidence: 99%
“…These enzymes catalyse the transfer of Sia (Neu5Ac or another derivative of sialic acid) from its activated sugar nucleotide donor, CMP-sialic acid, to an acceptor [90]. They govern addition of Sia with α-2,3-or α-2,6-linkage to the terminal galactose, with α-2,6-linkage to the terminal GalNAc or with α-2,8-linkage to the terminal Sias [99].…”
Section: Sialyltransferasesmentioning
confidence: 99%
“…To date, many sialyltransferases, and the genes encoding them, have been isolated from various sources including mammalian, bacterial, and viral sources (Schauer, 2004;Sujino et al, 2000;Yamamoto et al, 2006). During our research, we have isolated over 20 bacteria that produce sialyltransferase and have revealed the characteristics of these enzymes (Kajiwara et al, 2009;Yamamoto, 2010). In this chapter, we will introduce our research activities focusing on methods for (1) screening bacteria for glycosyltransferase activity; (2) purifying native sialyltransferases from marine bacteria; and (3) synthesizing and purifying sialyloligosaccharides produced by marine bacterial sialyltransferases.…”
Section: Introductionmentioning
confidence: 99%
“…GTs are potential drug targets (see, for example, [9]). In addition, their promiscuous substrate specificity in response to variations in the assay conditions is advantageous for in vitro glycan synthesis [23,24]. Experimental approaches for the identification of new GTs include the use of probes derived from the sequences of hitherto characterized GTs [25] and screening cell lysates for activity [26].…”
Section: Introductionmentioning
confidence: 99%